Réponses

2014-10-01T23:12:50+02:00
Exo 1
a) 2(x-12)-2=-5(x+4)
2x-24-2=-5x-20
2x+5x=26-20
7x=6
x=6/7

b) -2/5(x+1)+3/2=x/2+1/3
-2/5x-2/5+3/2=x/2+1/3
3/2-2/5-1/3=2/5x+x/2
45/30-12/30-10/30=(4/10)x+(5/10)x
23/30=9/10)x
x=(23/30)*(10/9)
x= 23/27

c) (3x+5)/6-(2x-12)/5=-2
(5*(3x+5)-6*(2x-12))/30=-2
15x+25-12x+72=-2*30
3x+97=-60
3x=-60-97=-157
x=-157/3

exo 2
à) (x+4)(2x-5)=0
2 solutions ¦ x+4=0 d'où x=-4 et 2x-5=0 d'où 2x=5; x=5/2

b) (-3/5x+2)(5/2x-1/5)=0
2 solutions ¦ -3/5x+2=0 d'où 3/5x=2; x=10/3 et 5/2x-1/5=0 d'où 5/2x=1/5; x=2/25

c) (√2x-5)(-2x-√3)=0
2 solutions ¦ √2x-5=0 d'où √2x=5; x=5/√2 et -2x-√3=0 d'où 2x=-√3; x=-√3/2

exo 3
a) (x+3)(x+5)-(x+3)(3x+1)=0
(x+3)(x+5-3x-1)=0
(x+3)(-2x-+4)=0
2 solutions x+3=0 d'où x=-3 et -2x+4=0 d'où 2x=4; x=2

b) (3x-9)(x+2)-(x-3)^2=0
3(x-3)(x+2-x-3)=0
3(x-3)(-1)=0
-3(x-3)=0
1 solution ¦ x-3=0 d'où x=3

exo 4
à) (2x-3)(x-2)-(5x+3)(2x-3)=0
(2x-3)(x-2-5x-3)=0
(2x-3)(-4x-5)=0
2 solutions ¦ 2x-3=0 d'où 2x=3; x=3/2 et -4x-5=0 d'où 4x=-5; x=-5/4

b) (x-6)^2-(6x+3)*2(x-6)=0
(x-6)(x-6-2*(6x+3))=0
(x-6)(-11x-12)=0
2 solutions ¦ x-6=0 d'où x=6 et -11x-12=0 d'où 11x=-12 ; x=-12/11

exo 5
a) (x-2)/(x+3)=0
1 solution x-2=0 d'où x=2

b) (x^2-9)=-(2x+6)(x+5)
(x-3)(x+3)+2(x+3)(x+5)=0
(x+3)(x-3+2x+10)=0
(x+3)(3x+7)=0
2 solutions ¦ x+3=0 d'où x=-3 et 3x+7=0 d'où 3x=-7; x=-7/3